Five-lipoxygenase-activating protein-mediated CYLD attenuation is a candidate driver in hepatic malignant lesion - Su, Kun-kai; Zheng, Xue-hua; Bréchot, Christian; Zheng, Xiao-ping; Zhu, Dan-hua; Huang, Rong; Zhang, Yan-hong; Tao, Jing-jing; Lou, Yi-jia; Li, Lan-juan (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is an inflammation-associated cancer. However, the lipid pro-inflammatory mediators have only been seldom investigated in HCC pathogenesis. Cylindromatosis (CYLD) attenuation is involved in hepatocarcinogenesis. Here, we aimed to evaluate the significance of hepatic lipid pro-inflammatory metabolites of arachidonate affected CYLD expression via 5-lipoxygenase (5-LO)-pathway. Resection liver tissues from HCC patients or donors were evaluated for the correlation of 5-LO/cysteinyl leukotrienes (CysLTs)-signaling to expression of CYLD. The impact of functional components in 5-LO/CysLTs cascade on survival of HCC patients was subsequently assessed. Both livers from canines, a preponderant animal for cancer research, and genetic-modified human HCC cells treated with hepatocarcinogen aristolochic acid I (AAI) were further used to reveal the possible relevance between 5-LO pathway activation and CYLD suppression. Five-LO-activating protein (FLAP), an essential partner of 5-LO, significantly overexpressed and was parallel to CYLD depression, CD34 neovascular localization, and high Ki-67 expression in the resection tissues from HCC patients. Importantly, high hepatic FLAP transcription markedly shortened the median survival time of HCC patients after surgical resection. In the livers of AAI-treated canines, FLAP overexpression was parallel to enhanced CysLTs contents, simultaneous attenuation of CYLD. Moreover, knock-in FLAP significantly diminished the expression of CYLD in AAI-treated human HCC cells. In summary, hepatic FLAP/CysLTs axis is a crucial suppressor of CYLD in HCC pathogenesis, which highlights a novel mechanism in hepatocarcinogenesis and progression. FLAP therefore can be explored for the early HCC detection and a target of anti-HCC therapy.